Gene expression analysis shows anticancer mechanism of Acacia podalyriifolia ethanol extract on MCF7 cells - Tedjo, Aryo; Rosmalena,; Fajrin, Ajeng Megawati; Azizah, Norma Nur; Elya, Berna; Najihah Mohd Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Breast cancer, particularly luminal A subtype, remains a significant challenge due to its resistance to certain therapies. Therefore, discovering new anticancer agents is critical. MCF7 cancer cells are commonly used as a model for studying luminal A breast cancer and screening potential anticancer compounds. This study aimed to investigate the anticancer potential of Acacia podalyriifolia leaves ethanol extract on MCF7 cells by exploring its effects on the expression of genes involved in the p53 signaling pathway. Differentially Expressed Genes (DEGs) analysis was performed on GSE208731 and GSE233242 obtained from the Gene Expression Omnibus (GEO) database to identify genes consistently regulated between MCF7 cells and luminal A breast cancer from patients or common DEG. The analysis identified several DEG, including CDKN1A (p21), GADD45A, CCNE1, CDK2, and E2F1, which are associated with the p53 signaling pathway. In this study, MCF7 cells were treated with IC50 dose of extract (154.52 μg/mL) was performed using the MTT assay. Then, gene expression analysis was performed using quantitative PCR (qPCR) to evaluate the impact on p53-related genes/common DEG. The extract significantly downregulated CCNE1 and E2F1, which are downstream genes in the p53 signaling pathway responsible for regulating the cell cycle. This downregulation led to cell cycle arrest and inhibited cell proliferation, suggesting the potential of Acacia podalyriifolia as a candidate anticancer agent for luminal A breast cancer.